1991
DOI: 10.1073/pnas.88.14.6382
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mast cell proliferation, maturation, and heparin synthesis by the rat c-kit ligand, stem cell factor.

Abstract: Induction of mast cell proliferation, maturation, and heparin synthesis by the rat c-kit ligand, stem cell factor (developmental ABSTRACTWe investigated the effects of a newly recognized multifunctional growth factor, the c-kit ligand stem cell factor (SCF), on mouse mast cell proliferation and phenotype.Recombinant rat SCF'64 (rrSCF"64) induced the development of large numbers of dermal mast cells in normal mice in vivo.Many of these mast cells had features of "connective tissue-type mast cells" (CTMC), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
236
2
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(256 citation statements)
references
References 37 publications
15
236
2
1
Order By: Relevance
“…The concentration of c-kit ligand or SCF, which is known to induce differentiation, aggregation, growth and activation of mast cells [37][38][39][40][41], was reduced by IL-10 gene transfer when compared to that in the acute myocarditis group, as seen in the immunohistochemical staining. Therefore, IL-10 gene transfer may have prevented mast cell degranulation and decreased the growth and density of mast cells via these mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of c-kit ligand or SCF, which is known to induce differentiation, aggregation, growth and activation of mast cells [37][38][39][40][41], was reduced by IL-10 gene transfer when compared to that in the acute myocarditis group, as seen in the immunohistochemical staining. Therefore, IL-10 gene transfer may have prevented mast cell degranulation and decreased the growth and density of mast cells via these mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the expression of GATA-1 was induced in BMMCs by two cytokines, IL-3 and SCF, which are known to induce growth and differentiation of BMMCs (Rennick et al 1995). SCF has been shown to induce BMMCs to acquire the characteristics of CTMCs which have high histamine and heparin content (Tsai et al 1991). In addition, GATA-1 is detected strongly in the nuclei of PMCs, which are another subtype of CTMCs.…”
mentioning
confidence: 99%
“…20,21,55 Maturation is dependent on a functional KIT receptor; 56 alternatively it is also mimicked by incubation of the mast cells with purified KL, but only upon IL3 withdrawal. 25 The maturation process can be monitored by the stage specific expression of mast cell proteases (MCP) from an immature to a more mature phenotype: the carboxypeptidase A protease (MC-CPA), the murine mast cell protease 6 (mMCP6), and the mMCP4 protease.…”
Section: Flt3 Is Able To Induce the In Vitro Maturation Of Mast Cellsmentioning
confidence: 99%
“…18 In hematopoietic differentiation, W mutants show defects in very early multilineage progenitors, early and late erythropoiesis, Correspondence: P Dubreuil; Fax: 33 491 260 364 Received 12 January 1997; accepted 3 January 1998 as well as in the development and function of mast cells. 18,19 Activation of KIT in normal mast cells stimulates different responses, their proliferation, [20][21][22] survival, 23 and/or differentiation. 20,21,24,25 KIT also participates in mast cell adhesion to extracellular matrix laid down by fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation